Role of weather on Alternaria Leaf Blight Disease and its effect on Yield and Yield Components of Mustard (Nepal Agriculture Research Journal, 2010)
Alternaria leaf blight disease caused by Alternaria brassicae in mustard (Brassica juncea (L)Czern and Coss) was studied in two crop seasons, 1992 and 1993 in Nepal at Nawalpur, Sarlahi(Tarai) and Khumaltar, Lalitpur (mid hill). At Nawalpur, epidemics of the disease was recorded forboth seasons. Weather conditions like humidity, temperature and frequent rainfall played key rolefor the epidemics. In experimental fields, the disease appeared first in mid-December when therelative humidity was more than 80% with maximum temperature ranging between 18-25°C andminimum between 10-14°C. At Khumaltar, incidence of the disease was low in both seasons due tolow average temperature from December to February. Among cultivars, Krishna and Pusabold wereless susceptible than Varuna. Both mancozeb and iprodione had effectively reduced disease in thesprayed plots and increased seed yield by 48% and 130% respectively. The correlation betweendisease severity and yield, and yield components was negative and highly significant. Average yieldloss was estimated to be in the range of 32 to 57%. Seed infection was also significantly higher innon sprayed treatment than sprayed one. The disease showed a negative effect on oil content causinglosses on oil between 4.2 to 4.5%.Key words: Alternaria brassicae; epidemics; iprodione; mancozeb; mustard; oil contentDOI: 10.3126/narj.v6i0.3366Nepal Agriculture Research Journal Vol.6 2005 pp.62-72